The Influence Of Leadership Style, Compensation, And Work-Life Balance On Organizational Performance: A Literature Review - Sinaga, Irma Suriyani; Hulu, Ruth Ansella Thalita; Nauli, Harum; Nauli, Kembang; Sitompul, Pandapotan (Jurnal Mirai Management, 2025)
This article aims to systematically review the academic literature on the influence of leadership style, compensation, and work-life balance on organizational performance within the context of Human Resource Management (HRM). Using a systematic literature review approach, the study analyzes empirical and conceptual findings from the past five years drawn from nationally accredited and internationally reputable journals. The results indicate that transformational and authentic leadership significantly enhance employee motivation and performance; fair and balanced compensation improves job satisfaction and loyalty; and effective work-life balance policies contribute to employee well-being and long-term productivity. These three variables interact and form a strategic HRM system that supports sustainable organizational effectiveness. The article also recommends further empirical research to examine causal relationships across various sectors and organizational contexts